Advances in Nucleic Acid Drugs and Gene Therapies based on Animal Models of Duchenne Muscular Dystrophy - LIU Siyu; LAI Yuezhao; GUO Wenting; CHEN Xuejin (Shiyan dongwu yu bijiao yixue)
Duchenne muscular dystrophy (DMD) is a severe X-linked recessive genetic disorder caused by mutations in the DMD gene, making it one of the most common forms of hereditary muscular dystrophy. The DMD gene, which encodes dystrophin, is the largest known gene in the human genome. Mutations in the DMD gene are highly diverse, including exon deletions, duplications, point mutations, and small insertions or deletions, posing significant challenges for treatment. Currently, there is no cure for DMD, and existing treatment strategies focus primarily on symptom management, which cannot reverse or halt disease progression. Advances in biotechnology position nucleic acid drugs and gene therapies at the forefront of DMD treatment research. These treatments aim to restore dystrophin expression by repairing or replacing mutated genes, thereby improving muscle function or slowing muscle degeneration. Preclinical studies in animal models and early-phase clinical trials demonstrate promising efficacy and offer new hope for DMD patients. This review briefly outlines the pathological mechanisms and genetic characteristics of DMD before delving into recent progress in therapeutic strategies, with a particular focus on nucleic acid drugs (including antisense oligonucleotides for exon skipping therapy and translation readthrough inducers) and gene therapy approaches (including gene replacement therapy and gene editing). The development and application of these therapies not only provide new treatment options for DMD patients, but also offer valuable insights for addressing other genetic disorders. However, numerous challenges impede the clinical translation of DMD treatments. Future studies must optimize existing therapeutic strategies, improve their efficacy and applicability, and explore innovative approaches to deliver more effective and sustainable treatments for DMD patients.